2015
DOI: 10.1007/s00429-015-1052-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anatomy of the thalamic complex and the underlying transcription factors

Abstract: Thalamocortical loops have been implicated in the control of higher-order cognitive functions, but advances in our understanding of the molecular underpinnings of neocortical organization have not been accompanied by similar analyses in the thalamus. Using expression-based correlation maps and the manual mapping of mouse and human datasets available in the Allen Brain Atlas, we identified a few individual regions and several sets of molecularly related nuclei that partially overlap with the classic grouping th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 117 publications
4
65
1
1
Order By: Relevance
“…This could be important given that each patient might contain a different subset of risk genes that produce dysfunction in different thalamic nuclei. The diversity of gene expression within the thalamus (Nagalski et al, 2016) could lead to the heterogeneity of the symptom set seen among patients. One of the most heterogeneous properties of the thalamus is the density of dopaminergic innervation (Garcia-Cabezas et al, 2009); thus, the synergistic action of genes affecting dopamine hyperfunction may be concentrated in a subset of thalamic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…This could be important given that each patient might contain a different subset of risk genes that produce dysfunction in different thalamic nuclei. The diversity of gene expression within the thalamus (Nagalski et al, 2016) could lead to the heterogeneity of the symptom set seen among patients. One of the most heterogeneous properties of the thalamus is the density of dopaminergic innervation (Garcia-Cabezas et al, 2009); thus, the synergistic action of genes affecting dopamine hyperfunction may be concentrated in a subset of thalamic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not support this hypothesis, because, in addition to Gbx2 and Pou4f2, subhabenular markers (e.g., Etv1) as well as sub-thalamic markers (e.g., Foxp2, Lef1, Prox1 and Rora) were downregulated in E18.5 Tcf7l2 -/embryos. Rora and Lef1 proved to be direct targets of TCF7L2 in ChIP-seq assay, and our previous in vitro results showed that TCF7L2 can regulate promoters of thalamic factors Gbx2, Pou4f1, Rora and Foxp2, and habenular Nr4a2 and Etv1 (Nagalski et al, 2016).…”
Section: Tcf7l2 and A Network Of Transcription Factors Regulate Morphmentioning
confidence: 52%
“…TCF7L2 is the only developmentally regulated transcription factor that is expressed throughout prosomere 2 postmitotically (Nagalski et al, 2016). TCF7L2 is not critically involved in the induction of pan-thalamic and pan-habenular identities that are defined by Gbx2 and Pou4f1 expression, respectively, because the expression of these markers was not abolished in Tcf7l2 KO embryos during neurogenesis (E12.5).…”
Section: Tcf7l2 and A Network Of Transcription Factors Regulate Morphmentioning
confidence: 99%
See 2 more Smart Citations